Design, Synthesis, and Antimycobacterial Activity of Novel Theophylline‐7‐Acetic Acid Derivatives With Amino Acid Moieties. (23rd November 2015) - Stavrakov, Georgi; Valcheva, Violeta; Voynikov, Yulian; Philipova, Irena; Atanasova, Mariyana; Konstantinov, Spiro; Peikov, Plamen; Doytchinova, Irini
Abstract : The theophylline‐7‐acetic acid (7‐TAA) scaffold is a promising novel lead compound for antimycobacterial activity. Here, we derive a model for antitubercular activity prediction based on 14 7‐TAA derivatives with amino acid moieties and their methyl esters. The model is applied to a combinatorial library, consisting of 40 amino acid and methyl ester derivatives of 7‐TAA. The best three predicted compounds are synthesized and tested against Mycobacterium tuberculosis H37Rv. All of them are stable, non‐toxic against human cells and show antimycobacterial activity in the nanomolar range being 60 times more active than ethambutol. Abstract : A model for antitubercular activity prediction was developed and applied to a combinatorial library of 40 theophylline‐7‐acetic acid derivatives. The best predicted compounds were synthesized and tested against Mycobacterium tuberculosis H37Rv. All of them showed antimycobacterial activity in the nanomolar range and were 60 times more active than ethambutol.